A new hypogean species of the genus Chaetomargoreicheia Magrini & Bulirsch, 2005 (Carabidae: Scaritinae: Clivinini) from Croatia - Ćurčić, Srećko; Pavićević, Dragan; Vesović, Nikola; Rađa, Tonći (Zootaxa, 2018)
Chaetomargoreicheia Magrini & Bulirsch, 2005 is a recently established genus of scaritine ground beetles (Bulirsch & Guéorguiev, 2008) (treated by certain authors as a subgenus of the genus Reicheadella Reitter, 1913) (Magrini & Bulirsch, 2005; Balkenohl, 2017) which currently contains two endogean species inhabiting the Balkan Peninsula: Chaetomargoreicheia zoufali (Reitter, 1913) and C. lakotai (Magrini & Bulirsch, 2005) (Balkenohl, 2003, 2017; Magrini & Bulirsch, 2005; Bulirsch & Guéorguiev, 2008). The aforementioned species are montane and inhabit confined geographic areas (Jeannel, 1957; Magrini & Bulirsch, 2005). C. zoufali was found only in the surroundings of the village of Ravno (collected beneath a deep layer of leaf-litter), Mt. Bjelasnica, near Trebinje, E Herzegovina (Bosnia and Herzegovina), while C. lakotai was found at the entrance of a cave nearby a road (collected under a huge stone), in Mt. Lovćen, near Kotor, S Montenegro (Reitter, 1913; Holdhaus, 1924; Jeannel, 1957; Magrini & Bulirsch, 2005). Chaetomargoreicheia species represent quite rare, stenoendemic taxa, for each of the up-to-now known species only one specimen has been collected by hand so far (Reitter, 1913; Jeannel, 1957; Magrini & Bulirsch, 2005). The fourth author of the current study investigated numerous underground and endogean high-altitude habitats in Dalmatia (Croatia) in the last few years. As a result of the exploration, he has recently collected a small sample of scaritine ground beetles from a cave in S Croatia. After thorough analysis of the sample, we have identified a new Chaetomargoreicheia species.